Climate-smart agriculture investment portfolios in Guyana: a way forward (Synthesis) - Navarrete Frías, Carolina; Lizarazo, Miguel; Eitzinger, Anton; Mwongera, Caroline; Sandoval, Danny; Rosales, Judith; Bullen, Pauline; Daggers, Louisa; Benn, Dina; Nanlall, Satesh (Bioversity International and the International Center for Tropical Agriculture, 2021)
Guyana is highly exposed to climate extremes with significant flooding risk for coastal regions, and more frequent drought events affecting subsistence agricultural activities in the hinterlands. Future climate scenarios show an increase in climate extremes. The agriculture sector requires a transformation toward climate-resilient agriculture systems. Gender and social inclusion are of great significance for the successful transformation to climate-resilient farming in Guyana. For Guyana’s agriculture to become more resilient against climate shocks, the government is focusing on improved water management for drainage and irrigation, creating decentralized infrastructure and services for farmers, and developing improved and innovative market mechanisms to improve farm income and livelihood diversification for smallholders. A way forward to resilience is to design Climate-Smart Agriculture (CSA) Investment Portfolios. CSA incorporates resilience through adaptation and mitigation measures while ensuring sustainable production and increased farm income.